A real-time pulse wave detection device basing on signal envelope - Ming Hong (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
We design a portable ECG (electrocardiograph) and PPG (photoplethysmograph pulse wave) measurement device which can simultaneously detect ECG and PPG signal, analyze arrhythmia and calculate SpO2 (oxygen saturation of blood). It consists of two parts: the main and the sub. MSP430 MCU is the most important part. Besides, there are front-end amplifiers, filter circuit, Bluetooth module, data management module, keyboard and LCD display module, etc. The device can detect QRS complex and PPG signals in real time. For the Fantasia database and patients, the monitor can correctly judge the QRS complex of ECG signals and pulse wave signal.